Comparative account on the length-weight and length-length relationships and condition factor of six cyprinid fishes from Dal Lake, Kashmir - Abrar Ahmad Bhat; Mohammad Yasir Arafat; Muni Parveen; Yahya Bakhtiyar (Journal of Fisheries, 2022)
Fish landings are routinely measured for length and weight to study fish bioecology, which provide important information about biomass, population dynamics and condition of fish. The current study describes the length-weight relationships (LWRs) and length-length relationships (LLRs) of six fish species (Cyprinus carpio, Carassius carassius, Schizothorax niger, S. curvifrons, Crossocheilus diplochilus and Pethia conchonius) based on seasonal fish sampling from the Dal Lake during September 2019 to August 2020. The estimated LWRs and LLRs were highly significant (p < 0.05) with high coefficient of determination r2 and the estimated b values ranged from 2.50 to 3.55. The estimated b values revealed negative allometric growth of fish species except P. conchonius which possesses positive allometric growth. The mean value of condition factor for C. carpio, C. carassius, S. niger, S. curvifrons, C. diplochilus and P. conchonius were 1.43±0.25, 1.55±0.24, 0.86±0.14, 0.80±0.13, 1.21±0.17 and 1.64±0.34 respectively and it varied significantly among these fish species (ANOVA: p < 0.05). The study shows LWRs, LLRs and current condition of some forage fish species viz., C. carassius, C. diplochilus and P. conchonius as well as invasive C. carpio and local Schizothorax species from the Dal Lake, all possessing economic and conservation significance.